Inner biblical allusion in the poetry of Wisdom and Psalms - Boda, Mark J. 1962-; Chau, Kevin ca. 21. Jh; Tanner, Beth LaNeel 1959- (T&T Clark, 2018)
"The contributors to this volume discuss not merely the theoretical aspects of the phenomenon of inner biblical allusion but rather provide practical examples of scholars working with specific texts within the Wisdom and Psalms corpora in order to showcase the function of this phenomenon within poetic texts. Closing responses from senior scholars (David Clines and John Goldingay) provide a critical engagement and mature reflection on the contributions"...
Includes bibliographical references and index
Keywords: Bible -- Psalms -- Criticism, interpretation, etc; Bible -- Psalms -- Comparative studies; Bible -- Wisdom of Solomon -- Criticism, interpretation, etc; Bibel -- Psalmen; Allusions in the Bible; Weisheitsliteratur; Intertextualität